The direct prognosis comparison of 125I low-dose-rate brachytherapy versus laparoscopic radical prostatectomy for patients with intermediate-risk prostate cancer - Liang, Zhen; Yuliang, Chen; Zhu, Ming; Zhou, Yi; Wu, Xingcheng; Li, Hanzhong; Fan, Bu; Zhou, Zhien; Yan, Weigang (European journal of medical research, 2023)
Background This study aims to compare the clinical outcomes after performing radical prostatectomy (RP) or low-dose-rate brachytherapy (LDR) for patients with intermediate-risk prostate cancer (IRPC). Methods We performed a retrospective analysis on 361 IRPC patients who underwent treatment in Peking Union Medical College Hospital from January 2014 to August 2021, of which 160 underwent RP and 201 underwent Iodine-125 LDR. Patients were followed in clinic monthly during the first three months and at three-month intervals thereafter. Univariate and multivariate regression analyses were conducted to predict biochemical relapse-free survival (bRFS), clinical relapse-free survival (cRFS), cancer-specific survival (CSS), and overall survival (OS). Biochemical recurrence was defined using the Phoenix definition for LDR and the surgical definition for RP. The log-rank test was applied to compare bRFS between the two modalities, and Cox regression analysis was performed to identify factors associated with bRFS. Results Median follow-up was 54 months for RP and 69 months for LDR. According to log-rank test, the differences of 5-year bRFS (70.2% vs 83.2%, P = 0.003) and 8-year bRFS (63.1% vs 68.9%, P < 0.001) between RP and LDR groups were statistically significant. Our results also indicated that there was no significant difference in terms of cRFS, CSS, or OS between the two groups. With multivariate analysis of the entire cohort, prostate volume [less than or equai to] 30 ml (P < 0.001), positive margin (P < 0.001), and percentage positive biopsy cores > 50% (P < 0.001) were independent factors suggestive of worse bRFS. Conclusions LDR is a reasonable treatment option for IRPC patients, yielding improved bRFS and equivalent rates of cRFS, CSS and OS when compared with RP. Keywords: Prostatic neoplasms, Low-dose-rate brachytherapy, Radical prostatectomy, Treatment outcomes, Comparative effectiveness